2000
DOI: 10.1080/10715760000300911
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical quantitation of UV-induced oxidative and dimeric DNA damage to human keratinocytes

Abstract: There is growing evidence to suggest that solar radiation-induced, oxidative DNA damage may play an important role in skin carcinogenesis. Numerous methods have been developed to sensitively quantitate 8-oxo-2'deoxyguanosine (8-oxodG), a recognised biomarker of oxidative DNA damage. Immunoassays may represent a means by which the limitations of many techniques, principally derived from DNA extraction and sample workup, may be overcome. We report the evaluation of probes to thymine dimers and oxidative damage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
0
26
1
Order By: Relevance
“…In these experiments, monochromatic lights of wavelength 320, 330 and 340 nm showed more toxic eŠects on ry 506 than the wild-type strain (unpublished observations). These results are not in agreement with previous reports (6)(7)(8). When Drosophila DNA in solution was irradiated with 20 kJ/m 2 of UVB light (302 nm peak wavelength), 8-OHdG residue levels increased 6-fold; however, there was no change in the response to irradiation with 300 kJ/m 2 of UVA (unpublished observations).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In these experiments, monochromatic lights of wavelength 320, 330 and 340 nm showed more toxic eŠects on ry 506 than the wild-type strain (unpublished observations). These results are not in agreement with previous reports (6)(7)(8). When Drosophila DNA in solution was irradiated with 20 kJ/m 2 of UVB light (302 nm peak wavelength), 8-OHdG residue levels increased 6-fold; however, there was no change in the response to irradiation with 300 kJ/m 2 of UVA (unpublished observations).…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, UVA is thought to induce mainly oxidative damage via formation of active oxygen species (5). In addition, UVA and UVB both induce oxidative damage, as revealed by an increase in the levels of 8-hydroxydeoxyguanosine (8-OHdG) residues in DNA from irradiated cells (6)(7)(8) and human epidermis (9). 8-OHdG is widely investigated as a maker of oxidative DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…(49) Our study demonstrated that UVA induced a dose-dependent increase in 8-OH-dG with a fixed concentration of 8-MOP in keratinocytes. PUVA produced both singlet oxygen and superoxide anions in an in vitro system.…”
Section: Discussionmentioning
confidence: 88%
“…The mechanism of UV radiation associated dermal damage includes, decreased collagen I and III synthesis, increased collagen degradation by TGF-β and activator protein A, infiltration of inflammatory cells predominantly by neutrophils into the dermis releasing ROS (Saha, 2012;Sorg et al, 2005;Talwar et al, 1995). Biomolecules weakly absorb UVA, but it can generate ROS, which oxidize proteins, DNA, and lipids (Cooke et al, 2000;Hattori et al, 1996;Struthers et al, 1998). Cells have developed defense systems to protect themselves from ROS, including endogenous, exogenous and enzymatic antioxidants (Dekker et al, 2005).…”
Section: Uv Rays and Skin Cancersmentioning
confidence: 99%